Using EMA and Calretinin on Cell Blocks for the Differentiation of Reactive Mesothelial Cells from Adenocarcinoma Cells in Pleural Effusions - Massood Hosseinzadeh; Neda Soleimani; Maryam Mohammadnia Avval; Perikala Vijayananda Kumar; Navid Omidifar; Mansoureh Shokripour; Sahand Mohammadzadeh (Journal of Kerman University of Medical Sciences, 2022)
Background: Effusion in body cavities can be considered as the presentation of malignancy or inflammatory conditions. Pleural fluid cytology is a popular diagnostic tool for the differentiation of adenocarcinoma cells (AC) from reactive mesothelial cells (RMC). However, there are many sources of controversies and errors in this technique that should be addressed.Methods: This case-control study aimed to evaluate the use of immunohistochemistry markers, namely epithelial membrane antigen (EMA) and calretinin, on cell blocks to differentiate between RMC and AC in pleural effusions. Suspected malignant effusions were selected according to the clinical data and their equivocal cytological smears. A total of 80 samples corresponding to the fresh specimens sent from the Department of Internal Medicine to the Cytology Laboratory of Faghihi Hospital during Jan 2017-Feb 2018 comprised the case group. In addition, the control group entailed 80 non-malignant pleural samples with RMC.Results: We observed that 74 (out of 80) effusion samples were strongly positive for EMA (92.5%). The sensitivity, specificity, and efficiency of the EMA marker were 92.5%, 95%, and 93.7%, respectively. The results of the calretinin assessment indicated 78 (out of 80) positive cases in the control group (97.5%). The sensitivity, specificity, and efficiency of calretinin staining were 97.5%, 98.7%, and 98.1%, respectively.Conclusion: According to the results of the current study, EMA and calretinin are two reliable markers with acceptable accuracy in differentiating between RMC and AC.